Bitter harvest : an inquiry into the war between economy and Earth - Krall, Lisi, 1954- (State University of New York Press, 2022)
Explores the duality between humans and Earth through a focus on the economic system changes that began with grain agriculture and has now reached its apogee in global capitalism.